LEVELS OF HOMOTYPIC NEUTRALIZING ANTIBODY IN HUMAN POLIOMYELITIS THREE YEARS AFTER INFECTION - Winsser, Johan (The Rockefeller University Press, 1952)
Quantitative neutralization tests in monkeys were carried out on sera obtained from 7 patients, 3 months, and 3 years after an attack of poliomyelitis. The serum specimens were tested against 100 to 1000 PD(50) of the patient's own strain of virus, recovered during the acute phase of the illness; all the strains were Type 1. The 6 patients, aged 6 months to 13 years, who had a paralytic attack of the disease, all exhibited very high levels of neutralizing antibody at 3 years as well as at 3 months after onset. The 50 per cent serum dilution titers ranged from about 1:180 to at least 1:860. Since the maximum titers were not established, it is not known to what extent, if any, the level of antibody may have dropped over the 3 year period. One of the patients, with a diagnosis of non-paralytic poliomyelitis, had a negligible or questionable antibody response during convalescence and no demonstrable antibody at 3 years; there is justifiable doubt as to whether the Type 1 poliomyelitis virus recovered from this patient had actually caused infection. Tests for Lansing neutralizing antibody indicated that the 5 patients who had no evidence of previous infection with Type 2 poliomyelitis virus had not become infected with it during the 3 year period. This suggested that these patients did not live in an environment in which infection with poliomyelitis virus is frequent. It is concluded, therefore, that in human beings, paralytic infections due to Type 1 poliomyelitis virus produce large amounts of homotypic neutralizing antibody, which persists at high levels for a period of at least 3 years.